2019
DOI: 10.1002/ejhf.1502
|View full text |Cite
|
Sign up to set email alerts
|

Clinical phenotypes of acute heart failure based on signs and symptoms of perfusion and congestion at emergency department presentation and their relationship with patient management and outcomes

Abstract: Objective To compare the clinical characteristics and outcomes of patients with acute heart failure (AHF) according to clinical profiles based on congestion and perfusion determined in the emergency department (ED). Methods and results Overall, 11 261 unselected AHF patients from 41 Spanish EDs were classified according to perfusion (normoperfusion = warm; hypoperfusion = cold) and congestion (not = dry; yes = wet). Baseline and decompensation characteristics were recorded as were the main wards to which patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 21 publications
0
70
0
2
Order By: Relevance
“…[3][4][5] Therefore, accurate profiling of patients admitted with AHF generates considerable interest in terms of designing clinical trials in the clinical settings of AHF. [6][7][8][9][10] Current European Society of Cardiology (ESC) Guidelines for diagnosis and treatment of acute and chronic heart failure (HF) recommend to classify patients with AHF according to clinical profiles, based on the presence or absence of congestion ('wet' vs. 'dry') and peripheral hypoperfusion ('cold' vs. 'warm') during bedside physical examination. 1,11,12 Prognostic value of the aforementioned clinical profiling has been recently confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Therefore, accurate profiling of patients admitted with AHF generates considerable interest in terms of designing clinical trials in the clinical settings of AHF. [6][7][8][9][10] Current European Society of Cardiology (ESC) Guidelines for diagnosis and treatment of acute and chronic heart failure (HF) recommend to classify patients with AHF according to clinical profiles, based on the presence or absence of congestion ('wet' vs. 'dry') and peripheral hypoperfusion ('cold' vs. 'warm') during bedside physical examination. 1,11,12 Prognostic value of the aforementioned clinical profiling has been recently confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Chioncel et al . and Javaloyes et al . reported prevalence and prognostic impact of clinical phenotypes based on perfusion and congestion status.…”
Section: Acute Heart Failure: Clinical Profiles Therapy and Self‐carementioning
confidence: 99%
“…Clinical profile of acute HF patients affects outcomes. 12 Chioncel et al 13 and Javaloyes et al 14 reported prevalence and prognostic impact of clinical phenotypes based on perfusion and congestion status. The phenotype 'wet-warm' was the most commonly observed.…”
Section: Clinical Phenotypes and Outcomesmentioning
confidence: 99%
“…[4][5][6][7] In addition, RD is usually presented together with other clinical situations which also worsen the prognosis. For example, there is the case of persistent congestion (which increases mortality, hospitalisation, hospital stay, rehospitalisation and resistance to loop diuretics) [8][9][10][11] or hyperpotassaemia (which, in addition to increasing mortality, limits the use of diseasemodifying drugs, such as renin-angiotensin-aldosterone system (RAAS) blockers or mineralocorticoid-receptor antagonists (MRAs). 12,13 Another comorbidity usually present is anaemia, thereby adding complexity to diagnostic and therapeutic management since it may be due to multiple conditions such as deficit in iron, cobalamins or folates, altered renal perfusion, reduced erythropoietin production or a situation of haemodilution due to congestion, all of which may be isolated occurrences or in combination.…”
Section: Introductionmentioning
confidence: 99%